Tax Farming : A Radical Solution for Developing Country Tax Problems? - Stella, Peter (IMF Working Papers; Working Paper ;, 1992)
Systemic tax administration problems in many developing countries have led to a search for radical solutions. One such proposed solution is tax farming. Tax farming is a system wherein the right to collect taxes is auctioned off to the highest bidder. An analysis of the historical experience with tax farming shows that its purported administrative efficiency is largely illusory. While certain aspects of tax administration may be suitable for privatization, the classic form of tax farming would appear to have little attraction for a modern state concerned with justice and equity.